Macroeconomic Impacts of Oil Price Fluctuations: Panel Data Evidence from Oil-Importing Developing Countries - Ahmad, Iftikhar; Bhatti, Muhammad Azhar; Rehman, Muhammad Atiq-ur; Ahmad, Tusawar Iftikhar (iRASD Journal of Economics, 2024)
This study reconnoiters the impact of oil price fluctuations on the macroeconomic performance of 95 oil-importing countries for the period 1981-2023. Due to an unobserved heterogeneity among the countries, the fixed effect approach of panel data estimation is employed. This approach is advantageous because it controls for the country-specific time invariant characteristics. According to our empirical findings, oil price fluctuations substantially affect GDP and Inflation. However, the coefficient on unemployment remains statistically insignificant. Our findings suggest that governmental policies should focus on reducing oil dependency by promoting renewable energy sources for improved macroeconomic performance and sustainable development.